Effects of carbon dioxide pneumoperitoneum on hepatic and renal morphology of rats after segmental colectomy and colonic anastomosis - Farias,Igor Eduardo Caetano (2011)
PURPOSE: To evaluate the effects of increased intraperitoneal pressure caused by carbon dioxide pneumoperitoneum on the hepatic and renal morphology of rats. METHODS: Fifty-four adult male rats were randomly divided into three groups (P, PP and C) after anesthesia: P - in 18 animals, pneumoperitoneum was established for 30 minutes immediately before laparotomy; PP - in 18 animals, pneumoperitoneum was established for 60 minutes divided into 30 immediately before laparotomy and 30 after abdominal closure; control group (C) - 18 animals underwent laparotomy without pneumoperitoneum induction. The pneumoperitoneum was maintained at a pressure of 5 mm Hg. Nine animals in each group were killed on the 3rd and 7th postoperative days, when kidney and liver samples were collected for morphological analysis. The liver specimens were stained with hematoxylin and eosin (HE), and the kidney specimens, with HE and von Kossa. Blinded examiners analyzed the slides. RESULTS: No changes in renal morphology were found. Liver samples showed histological signs of degeneration in animals in the pneumoperitoneum groups killed on the 7th postoperative day (p=0.029). CONCLUSION: The CO2 pneumoperitoneum did not affect renal morphology but caused hydropic degeneration in the liver of animals killed on the 7th postoperative day.